Combined model-based topology optimization of stiffened plate structures via MMC approach. (15th October 2021) - Li, Linyuan; Liu, Chang; Zhang, Weisheng; Du, Zongliang; Guo, Xu
Highlights: A topology optimization approach of stiffened plate structure with various cross-sectional properties of stiffener is proposed. The geometric characteristics of stiffeners can be conveniently controlled using Moving Morphable Components description. Based on EFG method, the dynamic connection between the plate and the beam node can be realized directly. Compared with the purely solid optimization model, the proposed method can realize the topology optimization of the stiffened plate structure in an efficient and accurate way. Abstract: In the present work, a Moving Morphable Components (MMC)-based approach is proposed for topological design of stiffened plate structures, where the stiffeners are used as the building blocks of optimization. Unlike traditional approaches where three-dimensional solid model is often adopted for numerical analysis, in the proposed approach, beam model and plate model are adopted for the modeling of the stiffeners and base plate, respectively, in the context of Element-Free Galerkin (EFG) method. This treatment can not only reduce the computational cost associated with structural analysis substantially but also capture the concerned structural responses more accurately. Several numerical examples are provided to demonstrate the effectiveness and efficiency of the proposed approach. Grphical Abstract: Image, graphical abstract